ENHANCING CHILDREN’S ENGLISH VOCABULARY ACQUISITION THROUGH DIGITAL STORYTELLING OF HAPPY KIDS KINDERGARTEN OF PALEMBANG - Gaya, Tridinanti (PEOPLE: International Journal of Social Sciences, 2018)
Enhancing English vocabulary to early childhood is the main problem often faced by the teachers. So, the purpose of this study was to determine the enhancement of children’s English vocabulary acquisition by using digital storytelling. This type of research was an action research. It consisted of a series of four activities done in repeated cycles: planning, implementation, observation, and reflection. students of B group (5-6 years old) of Happy Kids Kindergarten of Palembang were the subject of this study. This research was done 3 times cycle. The methods used for data collection were observation and documentation. Analysis of the data was descriptive qualitative and quantitative. The finding showed that the digital storytelling learning activities could enhance the children’s English vocabulary acquisition. It based on data of the enhancement in pre-cycle was 37%, to 51% in Cycle I. In the Cycle II was % and in the Cycle III was 89.3%. Thus, an enhancement about 14% from the pre-cycle to Cycle I. The enhancement about 20% from the Cycle I to the Cycle II and the enhancement about 18.3% from the Cycle II to the Cycle III. The conclusion of this study was digital storytelling learning method could enhance children’s English vocabulary acquisition of B group of Happy Kids Kindergarten of Palembang. Therefore, digital storytelling can be considered as an alternative to improve English language learning in the classroom.